SOCIAL MEDIA AND ITS UTILIZATION FOR DA’WAH BY SELECTED MUSLIM SCHOLARS IN NORTHERN NIGERIA - Muhammad Maga Sule; Lawal Abdulkareem (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
Social media has become an integral component of Muslims' personal and public lives throughout the world. The paper looked at how selected Muslim scholars used social media platforms like Facebook, WhatsApp, Telegram, Twitter, YouTube, and Zoom to conduct Da'wah in Northern Nigeria, using a sample of scholars from the three geopolitical zones of Northern Nigeria, namely the North-West, North-Central, and North-East. The goal of this study is to see how Muslim academics in Northern Nigeria use social media for Da'wah. Northern Nigeria was chosen for this study because it is a crucial location with a long history of Islamic growth. In-depth surveys of various pages/channels on social media platforms were surveyed, and this was supplemented with observation and depth interviews to get data. The researchers chose twenty-one scholars for the study and conducted a poll on their different social media pages/channels to determine their level of social media technology use for Da'wah. The study's findings indicated that the sampled Muslim scholars found it convenient to electronically offer their teachings and to upload video and audio of their Da'wah lectures on various social media platforms. According to the findings, Muslim scholars should continue to use social media platforms to assist present the image of Islam and Muslims. Media sosial telah menjadi komponen integral dari kehidupan pribadi dan publik umat Islam di seluruh dunia. Makalah ini melihat bagaimana ulama Muslim terpilih menggunakan platform media sosial seperti Facebook, WhatsApp, Telegram, Twitter, YouTube, dan Zoom untuk melakukan Dakwah di Nigeria Utara, menggunakan sampel ulama dari tiga zona geopolitik Nigeria Utara, yaitu Utara-Barat, Utara-Tengah, dan Timur Laut. Tujuan dari penelitian ini adalah untuk melihat bagaimana akademisi Muslim di Nigeria Utara menggunakan media sosial untuk berdakwah. Nigeria Utara dipilih untuk penelitian ini karena merupakan lokasi penting dengan sejarah panjang pertumbuhan Islam. Survei mendalam dari berbagai halaman/channel di platform media sosial disurvei, dan ini dilengkapi dengan observasi dan wawancara mendalam untuk mendapatkan data. Para peneliti memilih dua puluh satu ulama untuk penelitian ini dan melakukan jajak pendapat di halaman/saluran media sosial mereka yang berbeda untuk menentukan tingkat penggunaan teknologi media sosial mereka untuk Dakwah. Temuan penelitian menunjukkan bahwa para cendekiawan Muslim sampel merasa nyaman untuk menawarkan ajaran mereka secara elektronik dan mengunggah video dan audio ceramah Dakwah mereka di berbagai platform media sosial. Menurut temuan tersebut, cendekiawan Muslim harus terus menggunakan platform media sosial untuk membantu menghadirkan citra Islam dan Muslim.